How does pollination mutualism affect the evolution of prior self‐fertilization? A model. (20th November 2014) - Lepers, Clotilde; Dufay, Mathilde; Billiard, Sylvain
<x xml:space="preserve">Abstract</x> The mode of pollination is often neglected regarding the evolution of selfing. Yet the distribution of mating systems seems to depend on the mode of pollination, and pollinators are likely to interfere with selfing evolution, since they can cause strong selective pressures on floral traits. Most selfing species reduce their investment in reproduction, and display smaller flowers, with less nectar and scents (referred to as selfing syndrome). We model the evolution of prior selfing when it affects both the demography of plants and pollinators and the investment of plants in pollination. Including the selfing syndrome in the model allows to predict several outcomes: plants can evolve either toward complete outcrossing, complete selfing, or to a stable mixed‐mating system, even when inbreeding depression is high. We predict that the evolution to high prior selfing could lead to evolutionary suicides, highlighting the importance of merging demography and evolution in models. The consequence of the selfing syndrome on plant–pollinator interactions could be a widespread mechanism driving the evolution of selfing in animal‐pollinated taxa.